2020
DOI: 10.1002/anie.202011198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Specific, Single‐step Cancer Cell Isolation with Multi‐Aptamer‐Mediated Proximity Ligation on Live Cell Membranes

Abstract: A single‐step method for isolation of specific cells based on multiple surface markers will have unique advantages because of its scalability, efficacy, and mildness. Herein, we developed multi‐aptamer‐mediated proximity ligation method on live cell membranes that leverages a multi‐receptor co‐recognition design for enhanced specificity, as well as a robust in situ signal amplification design for improved sensitivity of cell isolation. We demonstrated the promising efficacy of our method on differentiating tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 35 publications
0
72
0
Order By: Relevance
“…This non‐exclusive membrane input actuates the cellular machine to output false values, resulting in the on‐target off‐tumor phenomenon [3] . To improve the specificity of cell discrimination, many impressive studies have reported logic‐based control over dual and multiple markers, including associative toehold‐based signal amplification, [4] safe synNotch‐gated CAR‐T, [2a, 5] stimuli‐responsive protein assembly and signal transduction, [6] and the dual‐lock–one‐key strategy [7] . However, some typical tandem logic nanoplatforms consist of multiple freely diffusible molecular components in solution, thus resulting in low and slow logic response, especially when the systems have nonspecific and long‐term binding events [8] …”
Section: Figurementioning
confidence: 99%
“…This non‐exclusive membrane input actuates the cellular machine to output false values, resulting in the on‐target off‐tumor phenomenon [3] . To improve the specificity of cell discrimination, many impressive studies have reported logic‐based control over dual and multiple markers, including associative toehold‐based signal amplification, [4] safe synNotch‐gated CAR‐T, [2a, 5] stimuli‐responsive protein assembly and signal transduction, [6] and the dual‐lock–one‐key strategy [7] . However, some typical tandem logic nanoplatforms consist of multiple freely diffusible molecular components in solution, thus resulting in low and slow logic response, especially when the systems have nonspecific and long‐term binding events [8] …”
Section: Figurementioning
confidence: 99%
“…Additionally, DNA nanodevices have implemented their smart logic functions by evaluating protein receptors on cell surface. [20][21][22][23][24][25] However, such protein receptor-based logic nanodevices have the following limitations. First, the unknown spatial distribution of different membrane receptors severely hampers the spatially-controlled logic operation at the surface of specific cell types, thus affecting the accuracy of tumor identification.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of multicycle or multimolecular inputs will only increase the system's complexity and side reactions [13] . Single‐input autonomous nanostructures have not been developed to identify every cell line [3a, 4] . Third, most logic nanoplatforms have not yet fully realized “one cell one barcode” diagnosis and advanced synergistic killing to target cells because they are monovalent one‐bit biosensors [4, 11a, 12a] .…”
Section: Figurementioning
confidence: 99%
“…Well‐designed FRET will produce a 20–100‐fold fluorescent increase after separating the reporter from the quencher [19] . Thus, FRET can also be considered as a more facile turn‐on amplification strategy compared with rolling cycle reaction (RCR) and hybridized chain reaction (HCR) [4, 13b] . Herein we designed three FRET pairs on the three aptamers and their respective cDNAs as logic switches in response to multiple cDNA or marker inputs (Figure 3 a).…”
Section: Figurementioning
confidence: 99%